Factors influencing engagement in postnatal weight management and subsequent weight and well-being outcomes - Avery, Amanda; Hillier, Sarah; Pallister, Carolyn; Barber, Jennifer; Lavin, Jacquie (Mark Allen Healthcare, 2016)
Many women exceed gestational weight gain recommendations. Successful postnatal weight management decreases the risk of entering further pregnancies obese. This service evaluation investigates women’s motivations to lose weight postnatally, the weight loss achieved and impact on self-esteem. Methods: online survey using quantitative questions to determine motivation and lifestyle behaviours related to post-natal weight management in women attending a commercial weight management organisation. Weekly weights confirmed from digitally recorded data. Results: 1015 responded. Mean joining BMI was 33.3kg/m2 ± 5.85 and when surveyed 30.5kg/m2 ± 5.86, a change of -2.8 ± 0.1 kg/m² (p <0.01, 95% CI 2.76 – 3.11). 463 (45.7%) joined the groups between 6-26 weeks postnatal. Main motivators to lose weight were ‘to improve how I feel about my body size and shape’ (85.2%) and ‘improve self-confidence’ (76.6%) although only ‘to improve my health’ (65.6%) correlated with actual weight loss (0.114, p<0.01). Healthcare professional recommendation was less of a reason (6.5%). Improvements in self-confidence (77.6%), self-esteem (78.6%), wellbeing (85.2%) and body size/shape (70.1%) were reported. Conclusion: Women chose to engage to improve self-confidence, feelings about their body shape and health. There is an opportunity for healthcare professionals to encourage women early after giving birth to engage in weight loss and this may improve outcomes.